El estudio de la filosofía y la teología de Santo Tomás según la Lumen Ecclesiae de Pablo VI - Andereggen, Ignacio Eugenio María (Sapientia, 2014)
Acknowledging the value that St. Thomas Aquinas’ teachings have for our times begins with the great effort that Leo XIII realized through his encyclical Aeterni Patris. This recognition of St. Thomas’ importance for the Church was similarly emphasized by the following pontiffs; especially by St. Pius X, but also up to the recent popes, above all Paul VI and John Paul II. These pontiffs showed a great practical mindset by indicating St. Thomas, in particular for our day in age, as a guide for studies. This indication was also taken up by the Second Vatican Council, in which on two occasions, the council fathers pointed out the importance of having St. Thomas as a guide for modern day theological and philosophical studies. In Paul VI’s letter Lumen Ecclesia, we find fundamental themes which deal with present day circumstances: St. Thomas in the socio-cultural and religious context of his times; the perennial values of the doctrine and method of St. Thomas; and the example of the Angelic Doctor for our present day. According to Paul VI, and also to Pius XI, by honoring St. Thomas Aquinas we acknowledge the authority of the Church as teacher, and vice versa, by not doing so, there is an attitude, at least unconsciously speaking, of a distancing oneself from the authentic magisterial teaching of the Church. Therefore, to show the value of St. Thomas’ doctrine helps to protect and get to know the revelation better.